2017
DOI: 10.1136/bmjspcare-2016-001145
|View full text |Cite
|
Sign up to set email alerts
|

Dying at home of cancer: whose needs are being met? The experience of family carers and healthcare professionals (a multiperspective qualitative study)

Abstract: ObjectivesSupporting patients to die in the place of their choosing is an important aspect of end of life care. Our study set out to answer the question: ‘How does the home environment influence perceptions of quality of death, and the experience of caring for the dying at home, for family carers and healthcare professionals (HCPs)?MethodsA qualitative approach, using multiperspective interviews with bereaved family carers (n=15) and a nominated HCP (n=13) ensured depth of insight gained into supporting a home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
(34 reference statements)
2
22
0
Order By: Relevance
“…Earlier research has shown that the feeling of being unprepared, especially regarding knowledge of symptoms and decisions about medication management, can represent a considerable burden for many family caregivers (Funk et al, ; Rakic et al, ). The family caregivers in our study shared stories indicating that the dying person and his/her caregivers have different needs, and this is well known in the literature (Male, Fergus, & Stephen, ; Pottle et al, ). The need for information and the provision of practical support are two areas where patients' and family caregivers' opinions can differ.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Earlier research has shown that the feeling of being unprepared, especially regarding knowledge of symptoms and decisions about medication management, can represent a considerable burden for many family caregivers (Funk et al, ; Rakic et al, ). The family caregivers in our study shared stories indicating that the dying person and his/her caregivers have different needs, and this is well known in the literature (Male, Fergus, & Stephen, ; Pottle et al, ). The need for information and the provision of practical support are two areas where patients' and family caregivers' opinions can differ.…”
Section: Discussionsupporting
confidence: 63%
“…However, family caregivers who provide home‐based care may feel unprepared for the role and often neglect their own needs (Stajduhar & Davies, ). A study from Wales (Pottle, Hiscock, Neal, & Poolman, ) showed that while patients maintained a sense of normality by staying at home, family caregivers felt the opposite; their normality was lost. The patients' views and needs took precedence over those of the family caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…HCPs did not often attend proactively to the details of how patients and FCGs felt about managing medicines in the home, as well as the practical difficulties and concerns they confronted while doing so and the tensions and conflicting interests arising between patients and family members. 14,19,167 The challenges involved in managing medicines in the home can be intense, if not overwhelming, especially in the last weeks and days of life. 7,14,16,39,74 However, the realities of care remain overlooked in the policy and public 166 perpetuation of an idealised depiction of care at home as a prerequisite for accomplishing 'a good death'.…”
Section: The Burden Of Treatmentmentioning
confidence: 99%
“…HDAH reflects the total time spent out of acute and postacute care settings and is consistent with prior research on patient preferences to spend time at home at the EOL. 15,16,29,30 The COVID-19 pandemic has even further accelerated the push to deliver cancer care in the home environment, 31 highlighting the need to understand and measure how well providers and health systems are performing in providing care that is effective and consistent with patients' wishes. These findings suggest that HDAH is readily measurable, varies meaningfully among patients and providers, and is associated with other indicators of quality, including the use of hospice for patients at the EOL.…”
Section: Hrr Characteristics Associated With Hdah At Eolmentioning
confidence: 99%